KONSEP PENCIPTAAN MANUSIA MENURUT AL-QUR’AN DAN TEORI EVOLUSI DALAM PERSPEKTIF TAFSIR ILMI: STUDI KOMPARATIF ANTARA TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB DAN BUKU KERUNTUHAN TEORI EVOLUSI KARYA HARUN YAHYA - Muhammad Hotibul Umam; Muhammad Faris Al-Fajri Arifin; Attoriq Islami Pasha; Muhammad Sholahuddin Ali; Andi Rosa (Adisam Publisher, 2026)
The debate over the origins of humanity is one of the most crucial points of convergence between religious discourse and modern science. This study examines, through a comparative analysis, how the concept of human creation is articulated in two influential works: *Tafsir Al-Misbah* by M. Quraish Shihab and *The Collapse of the Theory of Evolution* by Harun Yahya. Using the framework of scientific exegesis as an analytical tool, this research traces how each author interprets the verses of the Qur’an concerning the creation of Prophet Adam, while simultaneously responding to the scientific claims of Darwin’s theory of evolution. The method employed is qualitative content analysis using a literature review and comparative approach. The findings of this study indicate that Quraish Shihab constructs his arguments through an open dialogue between the revealed text and scientific findings, adopting a cautious stance without hastily concluding that there is a contradiction. Conversely, Harun Yahya positions himself as a total rejectionist of evolution, employing a more apologetic and polemical approach. Both authors utilize the tradition of scientific exegesis, yet they depart from different epistemological premises and arrive at divergent conclusions. This article concludes that the dialogue between religion and science in the context of human creation requires a more integrative and scientifically honest methodological framework, rather than merely a confrontational one. The relevance of scientific exegesis in addressing the controversy over the first human remains significant, provided it is supported by adequate scientific understanding and mature textual hermeneutics.